Advancements in Morphological Verification: Evaluating a Novel Method for Pancreatic and Distal Bile Duct Tumour (Global Journal of Medical Research, 2024)
Abstract not found
Keywords: cancer; the head of the pancreas; distal common bile duct; obstructive jaundice; morphological verification; biopsy